2014
DOI: 10.1111/cen.12490
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of thyroid volume and nodular size during and after pregnancy in a severe iodine‐deficient area

Abstract: Thyroid nodules were present in 30·1% of pregnant women. While size of the single/dominant thyroid nodule increased significantly during pregnancy, the number of nodules did not change.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
13
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 39 publications
4
13
0
1
Order By: Relevance
“…However, Brunn et al applied 0.479 as an optimized conversion factor instead of π/6 [1][2][3][4][5][6]. We also used 0.479 as conversion factor in our study.The results of the measurements made in our study are shown in Table 1 in comparison with the values found in other studies.Sahin et al found that thyroid gland volume reached its maximum level (14.2 ± 7.9ml) in the third trimester and maintained this value for another 3 months after delivery (P < 0.001) [17]. In a study conducted by Tajtakova et al, 22mL of goiter was accepted as the limit, and ultrasound was performed at 4 days after delivery, and the volume of the thyroid gland was 3.1mL more than the control group (P < 0.01).…”
Section: Discussionmentioning
confidence: 96%
“…However, Brunn et al applied 0.479 as an optimized conversion factor instead of π/6 [1][2][3][4][5][6]. We also used 0.479 as conversion factor in our study.The results of the measurements made in our study are shown in Table 1 in comparison with the values found in other studies.Sahin et al found that thyroid gland volume reached its maximum level (14.2 ± 7.9ml) in the third trimester and maintained this value for another 3 months after delivery (P < 0.001) [17]. In a study conducted by Tajtakova et al, 22mL of goiter was accepted as the limit, and ultrasound was performed at 4 days after delivery, and the volume of the thyroid gland was 3.1mL more than the control group (P < 0.01).…”
Section: Discussionmentioning
confidence: 96%
“…Similarly in ALSPAC study [58] the incidence of materno-fetal outcomes were not signi icantly different among severely iodine de icient pregnant women (UIC < 50 μg/L) compared to the iodine suf icient group. Another frequently attributed impact of severe iodine de iciency before and during pregnancy is increased rates of goiter, thyroid nodules formation [59,60] and the induction of maternal hypothyroxinemia [61]. A few clinical studies indicate that iodine supplementation during pregnancy reduces maternal thyroid size [62] and the risk of maternal hypothyroxinemia [63,64].…”
Section: Iodine Defi Ciency and Pregnancy Outcomesmentioning
confidence: 99%
“…Las lesiones nodulares tiroideas son bastante comunes durante la gestación; aparecen de novo o las existentes aumentan de tamaño (21) . En áreas con deficiencia de yodo leve a moderada, la incidencia de nódulos tiroideos durante el embarazo varía de 3 % a 21 % (22)(23)(24) . En la embarazada, los nódulos tiroideos tienen criterios diagnósticos similares a las no gestantes, con la excepción de imágenes con agentes radiactivos.…”
Section: Diagnósticounclassified